Ekstrak Buah Lerak (Sapindus rarak) sebagai Sabun Antibakteri yang Ramah Lingkungan - Novitarini, Novitarini; Kresnapati, I Nyoman Bagus Aji; Akmi, Alfarizi Muzaifa (Jurnal Biotek, 2024)
Synthetic surfactants contribute to environmental pollution and can cause skin irritation, highlighting the need for natural biosurfactants. Lerak fruit (Sapindus rarak) shows promise as a biosurfactant due to its 28% saponin content and potential antibacterial activity. This study aimed to evaluate the antibacterial activity of lerak fruit extract using three parameters: inhibition zone, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) against Staphylococcus aureus (Gram-positive) and Pseudomonas aeruginosa (Gram-negative). The research utilized a Posttest Only Control Group Design to test the antibacterial activity of lerak fruit extract against skin-surface normal flora, specifically Staphylococcus aureus and Pseudomonas aeruginosa. All antibacterial activity results were analyzed using One-Way ANOVA in SPSS IBM version 22. The study found the MIC to be 6.25% for Gram-positive bacteria and 1.56% for Gram-negative bacteria. The MBC was determined to be 25% for Gram-positive bacteria and 50% for Gram-negative bacteria. At a 50% concentration, the inhibition zones against Gram-positive and Gram-negative bacteria were 21.53 mm and 22.13 mm, respectively. These results demonstrate that lerak fruit extract possesses strong antibacterial activity against both Gram-positive and Gram-negative bacteria. This research provides a foundation for developing environmentally friendly antibacterial soap formulations using lerak fruit extract.